2018
DOI: 10.1126/science.aat8127
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide isoform-level dysregulation in ASD, schizophrenia, and bipolar disorder

Abstract: Most genetic risk for psychiatric disease lies in regulatory regions, implicating pathogenic dysregulation of gene expression and splicing. However, comprehensive assessments of transcriptomic organization in disease brain are limited. Here, we integrate genotype and RNA-sequencing in brain samples from 1695 subjects with autism, schizophrenia, bipolar disorder and controls. Over 25% of the transcriptome exhibits differential splicing or expression, with isoform-level changes capturing the largest disease effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

101
1,089
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 955 publications
(1,231 citation statements)
references
References 145 publications
101
1,089
4
Order By: Relevance
“…Similarly, in human brain, genomic regions associated with schizophrenia are enriched for genes that show differential isoform usage across neurodevelopment 7 , implicating many schizophrenia-associated risk loci in the regulation of the expression of specific RNA transcripts. Consistent with these findings, examples of associations between psychiatric risk-associated loci and the abundance of novel, alternatively spliced transcripts are beginning to emerge [8][9][10] , complementing numerous reports of altered splicing patterns in the brains of psychiatric cases, compared to controls [11][12][13] .…”
Section: Introductionmentioning
confidence: 73%
“…Similarly, in human brain, genomic regions associated with schizophrenia are enriched for genes that show differential isoform usage across neurodevelopment 7 , implicating many schizophrenia-associated risk loci in the regulation of the expression of specific RNA transcripts. Consistent with these findings, examples of associations between psychiatric risk-associated loci and the abundance of novel, alternatively spliced transcripts are beginning to emerge [8][9][10] , complementing numerous reports of altered splicing patterns in the brains of psychiatric cases, compared to controls [11][12][13] .…”
Section: Introductionmentioning
confidence: 73%
“…These spatial definitions have to a large extent been based on cytoarchitectural features -such as differences in the density and form of cells -as well as chemoarchitectural definitions derived from distribution of key molecules such as neurotransmitters (5,6). Ongoing collective efforts in the field are now starting to reveal the details of neuron and region connections at the microscale and mesoscale level (4,7,8), and gene expression in the human brain (9,10). These tissue definitions and the resulting mouse brain atlases (11,12) have been essential for establishing the experimental framework to explore brain structure and function relationships, but have also resulted in debate and disagreement over the validity of expert-based region annotations (13).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to evaluate whether the regulation networks related to ASD models could be conserved in human, we examined the expression levels of the hub genes with the data generated in an integrated transcriptional study using data sets of 2,000 high‐quality postmortem brain samples of individuals with SCZ or ASD [Gandal et al, ]. The significance of the alteration of expression levels of the hub genes based on student's t ‐test were calculated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that these hub genes were involved in drug abuse, bipolar disorder, depressive disorder, SCZ, and autistic disorder, which are a group of closely related disorders that may share some similar pathomechanisms with ASD. Finally, to evaluate whether the regulation networks related to ASD models could be conserved in human, we examined the expression levels of the hub genes with the data generated in an integrated transcriptional study using data sets of 2,000 high-quality postmortem brain samples of individuals with SCZ or ASD [Gandal et al, 2018]. The significance of the alteration of expression levels of the hub genes based on student's t-test were calculated (Fig.…”
Section: Ppi Network Construction and Hub Genes Screeningmentioning
confidence: 99%